Effect of Ovario hysterectomy on serum enzymatic and hormonal profile in bitches suffering from Pyometra - DABHI, D M; DHAMI, A J; TANK, P H; KELAWALA, N H (The Indian Journal of Animal Reproduction, 2023)
Serum enzyme and hormonal profile was studied in bitches to evaluate it’s prognostic and therapeutic signifi.cance. The mean values of serum aspartate aminotransferase (AST) and serum alanine aminotransferase (ALT) were higher (69.43 ± 3.98 and 77.86 ± 7.70 IU/1, respectively) in bitches affected with pyometra as compared to healthy ones (33.60 ± 2.85 and 30.80 ± 1.39 IU/1). However, there was no difference in their profile between closed and open pyometra, and the levels drop a little following ovario-hysterectomy in affected animals. The serurri alkaline phosphatase (ALP) activity was also elevated in pyometric bitches than the normal ones (81.14 ± 7.93 vs 40.40 ± 3.87 KAU %). Serum total cholesterol concentration in pyometric bitches was significantly higher (P < 0.01) than that in normal bitches (263.86 ± 21.54 vs 190.70 ± 18.79 mg/di). Serum progesterone profile was three times elevated (9.42 ± 2.20 vs 3 .53 ± 1.07 ng/ml) and oestradiol-17b was only onehalf (364.14 ± 68. 71 vs 615.00 ± 170.15 pg/ml) in pyometric bitches than the normal ones. Moreover, the mean progesterone concentration was higher (P < 0.0 I) in cases of closed pyometra than the open ones ( 18.90 ± 3.41 vs 5.63 ± 1.83 ng/ml), while as the levels of oestradiol-17b, declined significantly at 8-15 days following ovario-hysterectomy due to removal of ovaries. It was concluded that increase in serum enzye profile along with cholesterol and progesterone occurs in pyometric bitches as compared to normal ones. There is drop in their values post-ovario-hysterectomy. It may serve as a diagnostic and prognostic value in canine pyometra.